Prototaip perisian PBK matematik interaktif (pecahan algebra) menggunakan pendekatan EIF - Ahmad, Norazlina (2004)
Mathematics is a subject that requires students to understand the concept of learning in a comprehensive way with forming a scheme on the concept. To achieve this goal, students have to understand the basic concepts and examples given. Then the students will have to do exercises given and some extra exercises on their own to strengthen their knowledge. In performing this learning process, a study was done on using the ElF approach in the PBK software prototype, also known as the Computer Assisted Learning - Algebra Fraction (PBK- PA) that contains topics on algebra fraction for semester one syllabus in Politeknik Malaysia. The ElF approach involves three stages, which are Explain (E), Instruct (/), and Facilitate (F) that must be implemented throughout the process. The PBK- PA prototype software also focus on the teaching and learning theory, teaching strategy and the use of multimedia technology. This prototype is developed using software as Microsoft Visual Basic6.0, Swish, Adobe Photoshop and Sound Forge. The outcome ofthis project is a PBK- PA software prototype that can help students to carry out the learning process effectively.